Data Observer: A guide to data that can help to inform evidencebased policymaking - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2024)
For many attempts to inform evidence-based policymaking (or policy-makers in general) researchers have to rely on already available (instead of newly collected) data. These data have to be reliable, accessible (at best, without high hurdles, and with low or no fees to be paid) and findable. One way that helps to find suitable data that are easily accessible (and hopefully reliable) is to look at the contributions published in the Data Observer series described in this paper.
Keywords: C81; 330; Data Observer; micro data; evidence-based policymaking